Pengaruh Insentif Pajak Dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Di Samsat Jakarta Timur Tahun 2023 - Permata, Michelle; Rahmi, Notika (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This study examines the influence of Tax Incentives and Tax Penalties on the Compliance of Motor Vehicle Taxpayers in the One-Stop Administration System in East Jakarta in 2023. Tax Incentives aim to eliminate penalties for late payments, while Tax Penalties are intended to prevent violations of Tax Regulations. The objective of this research is to analyze the impact of Tax Incentives and Tax Penalties on Taxpayer Compliance. The method used is a quantitative approach. The population in this study consists of 1,151,709 motor vehicle tax object owners in the One-Stop Administration System in East Jakarta, with a sample size of 100 respondents determined using the Slovin formula. Data was collected through questionnaires and analyzed using Instrument Tests, Classical Assumption Tests, and Hypothesis Testing with Multiple Linear Regression Analysis. The results show that the Tax Incentives variable (X1) has a significant effect of 19.6% on Taxpayer Compliance (Y), the Tax Penalties variable (X2) has a significant effect of 13.8% on Taxpayer Compliance (Y), and simultaneously, Tax Incentives (X1) and Tax Penalties (X2) have a significant effect of 26.8% on Taxpayer Compliance (Y).